Synthesis and Interface Activity of a Series of Carboxylic Quaternary Ammonium Surfactants in Hydraulic Fracturing. (3rd November 2019) - Dai, Shixin; Gong, Yufei; Wang, Feng; Hu, Pan
Abstract : Hydraulic fracturing is an important technology for the development of unconventional resources, while the foam fracturing plays an essential role for the oil recovery in hydraulic fracturing. To further explore the anion effect of quaternary ammonium cationic surfactants on their relative performances, four fatty acid surfactants were prepared (cetyltrimethylammonium acetate (CTAAC), cetyltrimethylammonium butyrate (CTABU), cetyltrimethylammonium hexanoate (CTAHE), and cetyltrimethylammonium caprylate (CTACA)). The effect of anions on surface tension and foaming properties were discussed, and the emulsion stability was also investigated. The experimental results were presented that the CTAAC possesses the highest surface activities compared with other members in the prepared surfactants. The critical micelle concentration (CMC) and surface tension at the CMC (γ CMC ) increase as increasing methylene segments in the anions, the maximum surface excess concentration (Γ max ), and minimum area per molecule (A min ) present an opposite trend with the increase of methylene segments. The CTAAC exhibits the best performances on foamability and foam stability than other synthesized surfactants at 70°C; the initial foam height (H 0 ) and the foam height ratio (R 3 ) at 0 min and 3 min are 34.9 cm and 52.9%, respectively; this is due to the lowest surface tension and shortest methylene segments. In addition, the emulsion stability was shown to follow the order of CTAAC>CTABU>CTAHE>CTACA.